To enrich elementary teachers with interactive methods, as well as to study the methods of teaching in modern schools - Bosimova Muazzam Baxtiyor qizi (Genius Journals, 2025)
This article explores the necessity of equipping elementary teachers with interactive teaching methods and examines how modern schools are transforming their pedagogical approaches to suit the dynamic needs of 21st-century learners. The study investigates various strategies such as collaborative learning, digital integration, and differentiated instruction and evaluates their impact on student engagement and achievement. Through literature review, methodological analysis, and field-based observations, this paper highlights the relevance of teacher development programs, innovative classroom practices, and modern assessment tools in fostering effective teaching and learning
Keywords: Interactive methods; elementary education; modern teaching strategies